2012
DOI: 10.1016/j.neurobiolaging.2011.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment ameliorated high-fat diet-induced Aβ deposition and memory deficit in APP transgenic mice

Abstract: The pathogenesis of Alzheimer's disease (AD) is tightly associated with metabolic dysfunctions. In particular, a potential link between type 2 diabetes (T2DM) and AD has been suggested epidemiologically, clinically, and experimentally, and some studies have suggested that exercise or dietary intervention reduces risk of cognitive decline. However, there is little solid molecular evidence for the effective intervention of metabolic dysfunctions for prevention of AD. In the present study, we established the AD m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
66
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 44 publications
9
66
0
1
Order By: Relevance
“…mice-In our recent study, voluntary exercise is shown to be a useful tool for preventing the progress of cognitive dysfunction and amyloid pathology in APP-HFD mice (7). Notably, voluntary exercise does not ameliorate HFD-induced hyperinsulinemia or hypercholesterolemia but improves glucose intolerance as well as cognitive impairment.…”
Section: Effects Of Diet Control On Metabolic Conditions Of App-hfdmentioning
confidence: 95%
See 4 more Smart Citations
“…mice-In our recent study, voluntary exercise is shown to be a useful tool for preventing the progress of cognitive dysfunction and amyloid pathology in APP-HFD mice (7). Notably, voluntary exercise does not ameliorate HFD-induced hyperinsulinemia or hypercholesterolemia but improves glucose intolerance as well as cognitive impairment.…”
Section: Effects Of Diet Control On Metabolic Conditions Of App-hfdmentioning
confidence: 95%
“…For example, a prospective study revealed that physical activity is protective against the development of cognitive impairment in AD and that the highest activity group showed a lowered incidence of AD (9). Recently, we also demonstrated that voluntary exercise ameliorates HFD-induced memory deficit and A␤ deposition in APP transgenic mice (7), indicating that interventions to reduce metabolic conditions can become the preventive method for AD. However, it still remains unknown what kind of intervention targeting metabolic conditions is more effective.…”
mentioning
confidence: 89%
See 3 more Smart Citations